2021
DOI: 10.1002/elan.202100018
|View full text |Cite
|
Sign up to set email alerts
|

Orange Peel Derived‐Nitrogen and Sulfur Co‐doped Carbon Dots: a Nano‐booster for Enhancing ORR Electrocatalytic Performance of 3D Graphene Networks

Abstract: Herein, nitrogen, sulfur co‐doped carbon dots (N,S−CDs) have been synthesized by a cost‐natural fabrication method using waste orange‐peel as a natural‐carbon‐precursor. N,S−CDs have been hydrothermally anchored to the three‐dimensional‐graphene‐networks (3D−GNs) to boost the electrocatalytic activity by a defective surface effect. Due to the synergistic utilization of heteroatoms, and effective mass‐transfer and improved transport kinetics resulting from interconnected 3D‐architecture, N,S−CDs anchored 3D−GNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(45 citation statements)
references
References 92 publications
(118 reference statements)
1
39
0
5
Order By: Relevance
“…Nanotechnology is now considered to be an important part of engineering processes in the world [ 37 , 38 , 39 , 40 , 41 , 42 ]. The unique properties of nanomaterials have led to their widespread application in industry and the design of engineering systems and have led to significant changes in various scientific fields [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is now considered to be an important part of engineering processes in the world [ 37 , 38 , 39 , 40 , 41 , 42 ]. The unique properties of nanomaterials have led to their widespread application in industry and the design of engineering systems and have led to significant changes in various scientific fields [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of peroxidase to assist in species identification is a relatively simple and effective. Studies have shown that peroxidases are involved in the physiological responses of plants to disease, insect, salt, and drought resistance as well as resistance to biotic stresses ( Jamali et al, 2014 ; Baghizadeh et al, 2015 ; Karaman, 2021 ; Karaman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This led to the use of tumor markers Li et al (2020a), Duan et al (2021), Li et al (2021), Wang et al (2021), which are chemical-based substances that reflect the presence of tumors. They are not found in normal adult tissues but only in embryonic tissues Karimi-Maleh et al (2021c), Karaman (2021), Karaman et al (2021), or are present in tumor tissues at levels that greatly exceed those found in normal tissues (Li et al, 2020b;Vajhadin et al, 2020). Their presence or quantitative changes can reveal the nature of tumors, lend to the understanding of tumor histogenesis, cell differentiation and cell function, which can provide assistance in tumor diagnosis, classification and treatment guidance.…”
Section: Introductionmentioning
confidence: 99%